How Communication Gadgets and Social Networking Activities can Influence The Attitude of Language Learners: A Case Study at Binus University - Wishnoebroto Wishnoebroto (Bina Nusantara University, 2012)
After the invention of PC and the internet, smart phones and tablet PC are the common gadgets that can be easily found among people in Indonesia. Besides its advantages, these instruments change the way users communicating to the others. Preliminary observation suggests that students who used IT or communication gadgets have developed a different attitude compared to those who are not. In writing for example, many young students today tend to write using the keyboard rather than handwriting. From the writer’s point of view, it is believed that the characteristic of these communication gadgets has influenced the way most young teenagers act, talk, and behave. The result of analysis of this paper has provided a clearer picture on the effect of certain technology toward the behavior of some students and teachers at BINUS University. The data gathered through qualitative observation from English Department students and English teachers at BINUS University shows that the presence of communication gadgets and social networking activities has changed the attitude especially concerning to learning preference.